P01.02 Serum-derived DNA methylation markers distinguish functional and invasiveness subtypes in patients harboring pituitary tumors. (6th September 2019) - Castro, A V; Wells, M; Asmaro, K; Sabedot, T S; Mosella, M S; Malta, T M; Nelson, K; Snyder, J; deCarvalho, A; Mukherjee, A; Chitale, D; Robin, A; et al.
Abstract: BACKGROUND: Molecular profiling of circulating biomarkers released by tumors has a relevant clinical value in central nervous system (CNS) tumors, but its feasibility has not been investigated in pituitary tumors (PT) despite being the second common intraaxial tumors of the CNS ( 15%). Although usually benign and slow-growing, they can be nonfunctioning and invade surrounding structures resulting in significant comorbidities. DNA methylation aberrations distinguish PT according to their functional status but their role in invasiveness is still unclear. Pre-surgical detection of clinically relevant molecular markers associated with tumor behavior can address current diagnostic and therapeutic challenges. We hypothesized that PT release cell-free DNA (cfDNA) into the bloodstream allowing for the profiling of epigenetic markers associated with relevant clinicopathological features. MATERIAL AND METHODS: Genome-wide methylome profile of paired serum cfDNA (EPIC array) and tissue from 13 patients with pituitary macroadenomas (9 males; median age: 62; 9 NFPT, 6 invasive) and 3 controls serum (patients with epilepsy). RESULTS: Unsupervised analysis of the serum methylome from patients harboring PT was distinct from controls and other diseases (hypopituitarism, glioma and colorectal cancer) and supervised analysis (Wilcoxon Rank-sum Test) identified significant differentially methylated probes (DMP) that segregated PT from control serum specimens. Nonfunctioning and invasive-specific DMPs identified in the serum also defined functional, and less prominently invasive status, in the tissue of an independent cohort of PT. CONCLUSION: This is the first study to show the feasibility to profile the methylome in the serum of patients with PT using cfDNA. In addition, we identified unique methylation signatures that distinguished PT according to functional and invasiveness subtypes. These results underpin the potential role of methylation profile and liquid biopsy as a noninvasive approach to assess clinically relevant molecular features in the serum of patients harboring PT.